ANALISIS KEAKSARAAN FUNGSIONAL MASYARAKAT DESA TANJUNG REJO: STUDI KUALITATIF DI KECAMATAN PERCUT SEI TUAN - Fira Aprilia; Fauzi Kurniawan; Anifah Anifah; Ayu Wulandari Siregar; Tari Patunnisa; Serasi Zendrato; Esra Haniarta Saragih; Sentia Br Malau; Desy Greace Sidebang; Tri Oktavia Siregar (Universitas Negeri Medan, 2025)
This study aims to analyze the level of functional literacy within the community of Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. Considering the importance of literacy as a foundation for human resource development and community empowerment, this research employs a qualitative descriptive approach to explore experiences and literacy practices in everyday life. The study involved 22 participants selected through purposive sampling technique. Data were collected through Focus Group Discussions (FGD), participatory observation using various learning media (shopping lists, play money, financial records), and village documentation study. The results indicate that the Tanjung Rejo Village community possesses good literacy levels across three tiers: (1) Basic Literacy - 15 out of 22 people can read, write, and match item names with pictures; (2) Advanced Literacy - 18 out of 22 people can record financial transactions and calculate change; and (3) Functional Literacy - all 22 participants can analyze weekly income-expenditure comparisons and create financial plans. Documentation study confirms that there are no recorded illiterate individuals in this village, with all participants having senior high school educational backgrounds. These findings indicate that the Tanjung Rejo Village community has adequate functional literacy to manage daily life, particularly in household financial management aspects. This study recommends literacy improvement programs that focus more on digital literacy and entrepreneurship to optimize the potential of the already literate community.